Serum procalcitonin as a diagnostic marker in acute ischemic stroke. Issue 1 (7th January 2015) - Tian, Da; Zhang, Shengwu; He, Xuwei; Liu, Hong
Abstract : The aim of the study was to assess the relationship between procalcitonin (PCT) serum levels and acute ischemic stroke (AIS) in a Chinese sample. All consecutive patients with first-ever AIS between January 2012 and December 2013 were recruited to participate in the study. PCT levels and National Institutes of Health Stroke Scale scores were evaluated at the time of admission. Logistic regression analysis was used to evaluate the risk for stroke according to serum PCT levels. The results indicated that serum PCT levels were significantly higher in AIS patients as compared with normal controls ( P <0.0001). PCT levels increased with increasing severity of stroke, as defined by the National Institutes of Health Stroke Scale score. After adjusting for all other possible covariates, PCT level was found to be associated with an increased risk for AIS, with an adjusted odds ratio of 2.244 (95% confidence interval 1.563–3.756, P <0.0001). On the basis of the receiver operating characteristic curve, the optimal cutoff value of serum PCT levels as an indicator for auxiliary diagnosis of AIS was projected to be 1.20 ng/ml, which yielded a sensitivity of 79.6% and a specificity of 72.1%, with the area under the curve at 0.801 (95% confidence interval 0.762–0.844). An elevated serum level of PCT was a novel, independent diagnostic marker of AIS in the Chinese sample. Further study is needed to confirm these results.